2018
DOI: 10.48550/arxiv.1810.04538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secure Deep Learning Engineering: A Software Quality Assurance Perspective

Abstract: Over the past decades, deep learning (DL) systems have achieved tremendous success and gained great popularity in various applications, such as intelligent machines, image processing, speech processing, and medical diagnostics. Deep neural networks are the key driving force behind its recent success, but still seem to be a magic black box lacking interpretability and understanding. This brings up many open safety and security issues with enormous and urgent demands on rigorous methodologies and engineering pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…We confirmed the usefulness of the proposed criteria on ASRs and showed that the fuzzing framework is effective in exposing real-world defects. In the future, we plan to evaluate our techniques on more diverse application domains, towards providing quality assurance solution for DL systems life-cycle [57].…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed the usefulness of the proposed criteria on ASRs and showed that the fuzzing framework is effective in exposing real-world defects. In the future, we plan to evaluate our techniques on more diverse application domains, towards providing quality assurance solution for DL systems life-cycle [57].…”
Section: Discussionmentioning
confidence: 99%
“…Although over the past few years deep learning has been the key driving force in self-driving industry, it also raises safety and security issues due to the lack of interpretability and transparency [27]. Stop line detection is a safety-critical application, and hence understanding how the network retrieves information from different channels and makes decisions is very crucial.…”
Section: F Visual Interpretationmentioning
confidence: 99%
“…DeepStellar [11] employs the coverage criteria and fuzzing technique for testing the recurrent neural network. More discussions on the progress of deep learning testing can be referred to the recent survey [67,38]. Different from these testing techniques, our work mainly focuses on repairing DNNs and enhance their robustness and generalization ability, which can be considered as the downstream tasks of DNN testing.…”
Section: Dnn Testingmentioning
confidence: 99%